Investigating the impact of age and sex on cataract surgery complications and outcomes - Hadas Ben-Eli; Yaacov Cnaany; Michael Halpert; Itay Chowers; Ayelet Goldstein (Scientific Reports)
Abstract Cataract surgery, a common procedure for vision restoration, exhibits variable outcomes based on patient demographics. This study aimed to elucidate the effects of age and sex on risk factors, intraoperative complications, and postoperative outcomes of cataract surgery. A single-center retrospective cohort study analyzed 691 eyes from 589 individuals who underwent surgery at a tertiary referral center, using electronic medical records to assess preoperative risk factors, intraoperative complications, and best corrected visual acuity (BCVA) pre- and post-operatively, alongside demographic data. The study found that males aged 65–75 years had significantly higher rates of functional postoperative BCVA (91% for males vs. 79% for females, p = 0.007), a disparity not attributable to differences in surgical complications or risk factor prevalence. Age-specific thresholds were identified where BCVA improvements significantly declined beyond 65 years for females and 75 years for males. The likelihood of worsened BCVA post-surgery increased with age for both sexes, with a notable decline in BCVA improvement between the 55–65 years and 65–75 years age groups. These findings underscore the critical influence of sex and age on cataract surgery outcomes, advocating for the integration of these factors into preoperative evaluations to better tailor the timing and planning of cataract surgery and optimize clinical outcomes.